Development of Colloidal Gold-Based Immunochromatographic Assay for Rapid Detection of Goose Parvovirus - Yu, Xianglong; Wei, Lei; Chen, Hao; Niu, Xiaoyu; Dou, Yanguo; Yang, Jing; Wang, Zhenzhong; Tang, Yi; Diao, Youxiang (Frontiers in Microbiology, 2018)
Goose parvovirus (GPV) remains as a worldwide problem in goose industry. For this reason, it is necessary to develop a new diagnostic approach that is easier and faster than conventional tests. A rapid immunochromatographic assay based on antibody colloidal gold nanoparticles specific to goose parvovirus was developed for the detection of GPV in goose allantoic fluid and supernatant of tissue homogenate. The monoclonal antibodies (Mab) was produced by immunizing the BALB/c mice with purified GPV suspension, and the polyclonal antibody(pAb) was produced by immunizing the rabbits with recombinant VP3 protein. The colloidal gold was prepared by the reduction of gold salt with sodium citrate coupled with Mab against GPV. The optimal concentrations of the coating antibody and capture antibody were determined to be 1.6 mg/ml and 9 μg/ml. With visual observation, the lower limit was found to be around 1.2 μg/ml. Common diseases of goose were tested to evaluate the specificity of the immune colloidal gold (ICG) strip, and no cross-reaction was observed. The clinical detection was examined by carrying out the ICG strip test with 92 samples and comparing the results of these tests with those obtained via agar diffusion test and polymerase chain reaction(PCR) test. Therefore, the ICG strip test was a sufficiently sensitive and accurate detection method for a rapid screening of GPV.